Exploring The Potential Of Virtual Reality For R Programming Education - Abdulrazak Yahya, Saleh; Siew Peng, Soo (2025)
This study develops and evaluates a novel Virtual Reality (VR) system for teaching fundamental R programming skills to university students, addressing common learning challenges. Grounded in Experiential Learning Theory and constructivism, our system aims to leverage immersive environments for enhanced knowledge construction. Employing a quasi-experimental design, we compared the efficiency of VR-based and traditional R learning methods among fifty 21-27 year-old participants. Participants were divided into two groups: one utilizing conventional methods and the other the VR system, developed with Unity 3D using a Rapid Application Development (RAD) approach and implemented on Oculus Quest 2 for an immersive experience. Evaluation involved hypothesis tests, the System Usability Scale (SUS), and Presence Questionnaires (PQ). Findings demonstrate that VR-based learning significantly enhanced performance over traditional methods, with a t-statistic of 2.741 (exceeding the t-critical value of 2.011) and a large Cohen's d effect size of 0.78. Additionally, 40% of participants rated the VR system above 68/100, indicating high satisfaction. Overall, the VR method proved to be an effective, convenient, and engaging tool for R coding education.